Learning Istima' Kalam Using Multimedia on Student Achievement at Ma'arif Bangsalsari Vocational School - Zainuri, Zainuri; Rosyadi Abdul Jalil Mannan, Ahmad Mizan; Furoidah, Asni; Nabiilah, Alaikin (UAS PRESS, 2025)
The problem faced by teachers is the limitation in providing Arabic language learning media. This problem causes a lack of motivation to learn so that students' understanding and knowledge are low. Efforts are made to develop audio-visual technology in Arabic language learning. The purpose of this research is to describe the implementation of Maharah Istima' learning using multimedia on the achievement of SMK Ma'arif Bangsalsari students by describing the learning process in each stage. This research is analytical and prioritizes the research process on the implementation of Maharah Istima' Kalam learning with multimedia on class X students of SMK Ma'arif Bangsalsari Jember so that a qualitative approach is more appropriate to use. that students are able to practice the learning of Istima' Kalam that has been taught to improve student achievement at SMK Ma'arif Bangsalsari. so according to the presentation above, it shows the results of student learning that students who are less able, able and very able in learning Istima' Kalam to improve student achievement The teachers use several media, one of which is media in learning, the results show that students are able to practice the learning of Istima' Kalam that has been taught to improve student achievement at SMK Ma'arif Bangsalsari. Based on the results of student learning in learning istima' kalam is declared successful.